ORTHO-CHLOROANILINE DEGRADATION UNDER THE INFLUENCE OF OZONE IN AQUEOUS SOLUTION - Ermin Katrin Winarno (Indonesian Journal of Chemistry, 2007)
The degradation study on 2-chloroaniline (2-ClA) used as a model of water pollutant by ozonation was performed. The change of spectrum and substrate concentration of treated solutions were measured by spectrophotometer as well as by HPLC method. The change of solutions pH after ozonization was observed. The yields of the products formed (chloride ions, ammonium ions, and formaldehyde) were investigated as a function of ozonation time. The results showed that the ozonation gave to an efficient degradation of 2-ClA.